Role of nanomaterials in food authentication techniques: A mini-review - M. A. , Motalib Hossain (Malaysian NANO-An International Journal, 2024)
Food authentication is critical for ensuring food safety, quality, and compliance with regulatory standards. The growing complexity of food supply chains and increasing incidents of food fraud necessitate advanced and reliable methods for verifying food authenticity. Nanomaterials (NMs) have emerged as powerful tools in food authentication due to their unique physicochemical properties. This mini-review explores the application of various NMs, including metal nanoparticles (NPs), carbon-based NMs, and quantum dots, in the detection and identification of food adulteration and contamination. The review highlights recent advancements, practical applications, and future prospects of NMs in enhancing food authentication techniques. In this review, we explore the latest advancements in the application of NMs in food analysis. We summarize recent developments in NP usage for detecting contaminants in food and highlight the prospects and future directions for creating dependable devices for authentic analysis.